Application of virtual simulations in the practical teaching of clinical microbiology laboratory courses - Jiaxue Wang; Yunshui Jiang; Jun Yang; Qian Zhou; Hui Hu; Yan Chen; Jinqin Jiang (BMC Medical Education)
Abstract This study implemented a novel virtual simulation operation (VSO) teaching platform to enhance offline teaching in clinical microbiology laboratory courses, specifically addressing biosafety level-3 (BSL-3) for SARS-CoV-2 isolation and culture. The study focused on the practical teaching component, comparing the effectiveness of VSO against traditional online video teaching. The study divided undergraduate medical laboratory technology students into experimental and control groups. The experimental group received teaching combining offline courses with online VSO exercises, while the control group participated in offline courses supplemented with standard teaching video reviews. Assessment criteria included comprehensive practical performance, operational skills, laboratory biosafety awareness, and aseptic awareness. An anonymous questionnaire evaluated teaching effectiveness. The integration of VSO with offline practical teaching demonstrated significant improvements in student performance, particularly in comprehensive practical skills, experimental operations, and laboratory biosafety awareness. These findings validate the effectiveness of this virtual simulation teaching platform as an innovative educational tool, offering valuable insights for curricular reform across other disciplines.